Emission Inventory of Greenhouse Gases in Yogyakarta for Transportation Sector - Maulana Khafid Arrohman (Publikasi Indonesia, 2025)
D.I. Yogyakarta is one of the major provinces in Java, Indonesia, with a population of 3.8 million in 2020. The region is characterized as an education and tourism hub, which has driven continuous growth in transportation activities. The number of registered vehicles in Yogyakarta in 2020 reached approximately 3.5 million units, with motorcycles contributing more than 80% of the total. The increase in motor vehicle usage has raised concerns about the contribution of the transportation sector to greenhouse gas (GHG) emissions and air pollution. However, total emissions from this sector are not well documented. This study estimated GHG emissions from the transportation sector in Yogyakarta. The policy interventions such as EURO IV implementation was evaluated to assess their effectiveness in reducing emissions. The results for 2015 data show that total emissions from the transportation sector reached approximately 2.05 Mt GHGs/year. The implementation of EURO IV alone shows a relatively limited reduction, therefore it is expected that this scenario be combined with other control measures such as the adoption of electric vehicles, CNG, electronic road pricing (ERP), and other complementary strategies.